Circuit modeling for electromagnetic compatibility - Darney, Ian B. (SciTech series on electromagnetic compatibility, 2013)
This book shows how the analytic tools of circuit theory can be used to simulate the coupling of interference into, and out of, any signal link in the system being reviewed. The technique is simple, systematic and accurate. It enables the design of any equipment to be tailored to meet EMC requirements. Every electronic system consists of a number of functional modules interconnected by signal links and power supply lines